Improve Organizational Performance by implementing Competency Based Empowerment for Employees - Budiman (GoAcademica Research & Publishing, 2019)
This study aims to analyze empowerment strategies for increasing employee competence. This research uses a qualitative approach and descriptive methods. The data were obtained through a literature review and analyzed descriptively and qualitatively. The results showed that employee competence could be improved through employee empowerment, such as: providing information on employee competencies; creating a culture of organizational climate that supports optimal employee competence; provide full support to employees so that they can serve their roles and actualize their competencies optimally; encourage participation in organizational activities; provide access to the widest possible information; encourage the growth of innovation by enabling and providing opportunities to express every innovative and potential idea that can enrich their competence, and encourages high accountability.